Distribution and Numbers of Three Globally Threatened Waterbird Species Wintering in Morocco: The Common Pochard, Marbled Teal, and White-Headed Duck - Ouassou, Asmaâ; Dakki, Mohamed; El Agbani, Mohammed-Aziz; Qninba, Abdeljebbar; El Hamoumi, R’himou (International Journal of Zoology, 2021)
Morocco plays a key role in the life of many migratory birds and their survival, thanks to the diversity and richness of its ecosystems. The International Waterbird Census (IWC) has been regularly implemented in Morocco since 1983. Thanks to this program, a large database on wintering waterbirds’ populations has been collected. In this article, we summarize the wintering data of three globally threatened waterbirds: Aythya ferina, Marmaronetta angustirostris, and Oxyura leucocephala. The population of Aythya ferina, which is declining, is largely distributed in the country, in over a hundred wetlands, 26 of which verify the national importance criteria. Marmaronetta angustirostris has a stable trend over the years even though its population can know high annual fluctuations; it winters in more or less 50 wetlands, among which 18 host more than 1% of its regional population and 16 verify the criteria for national importance. On the contrary, Oxyura leucocephala, a globally endangered bird only encountered in a dozen wetlands, shows a moderate increase in its numbers; only two wetlands verify the Ramsar criterion 6, while a total of six can be considered of national importance. Furthermore, given the conservation statuses of these waterbirds and according to the Ramsar criterion 2, all their hosting sites are of international importance. The results presented in this paper are a crucial step for the adoption and implementation of adequate conservation measures for the species and their key sites. Nevertheless, comprehensive research and coordinated efforts on the factors (ecological and anthropogenic) influencing the species, at the national and international levels, are required for a better understanding of their populations’ dynamics.